Civil society and local democracy in Yogyakarta, Indonesia - Suyatno, , (2013)
In an era global change, the development of civil society encourages democracy, in particular in local level.Transparency, partnership and accountability become pivotal issues that covering political process. Local government cannot avoid anymore the role of local civil society in decision making process.Not only is caused by the enhancement of civil society that is influenced by global change, but also local government need partnership to alleviate burden.In Yogyakarta city, walikota (mayor) involves civil society to make political decision, in particular in crucial problem.For example, the policy of moving street vendor from Mangkubumi street to Pakuncen area.Local government gives widely spaces for civil society lo play their role to mediate conflict between pro its policy and contra its policy.Partnership between local government and civil society succeed to find best solution that avoids violence.This paper want to describe the role of local civil society and local government to overcome some problems and involvement among them to build partnership in decision making process that produce benefit policy for society at local level.Using transparency and accountability policies, local government in Yogyakarta city succeed to implement some policies that describing good relations among state and society.Partnership policy that built among local government and civil society become important basic for enhancement of local democracy.